2021
DOI: 10.1136/bmjopen-2020-047920
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of mid-life to elderly adulthood BMI and incident hypertension: the China Health and Nutrition Survey

Abstract: ObjectivesThis study is designed to identify different body mass index (BMI) trajectories of individuals aged 40–70 years and test the effect of distinct BMI trajectories on incident hypertension.DesignThe accelerated longitudinal design was used for this study.MethodsThe study drew data from the third to ninth China Health and Nutrition Surveys (CHNS), and 4697 participants were included between 1991 and 2015. As analysed, three distinct individual BMI trajectories were identified by the latent class growth m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 36 publications
3
10
0
Order By: Relevance
“…Trajectories of BMI and WC allow the assessment of dynamic patterns of BMI and WC and the impact on hypertension [ 22 ]. Based on the findings of previous studies on BMI trajectories in adults, trajectories of rapidly increasing BMI in Chinese [ 23 ] and trajectories of maintaining high BMI levels in Chinese [ 24 ] and in Canadians [ 25 ] are associated with an increased risk of hypertension. Cheng et al [ 26 ] found that sharply increasing trajectories of WC during adolescence were associated with higher risks of incident hypertension in Chinese.…”
Section: Introductionmentioning
confidence: 99%
“…Trajectories of BMI and WC allow the assessment of dynamic patterns of BMI and WC and the impact on hypertension [ 22 ]. Based on the findings of previous studies on BMI trajectories in adults, trajectories of rapidly increasing BMI in Chinese [ 23 ] and trajectories of maintaining high BMI levels in Chinese [ 24 ] and in Canadians [ 25 ] are associated with an increased risk of hypertension. Cheng et al [ 26 ] found that sharply increasing trajectories of WC during adolescence were associated with higher risks of incident hypertension in Chinese.…”
Section: Introductionmentioning
confidence: 99%
“…Other study conducted by Zeng et al (2021), which also assessed various BMI trajectories in relation to the incidence of HBP, the adjusted HR for HBP was compared to the stable low BMI class. The findings revealed that the sharply increasing BMI class had an adjusted HR of 1.3 (95%CI: 1.1-1.5), while the stable high BMI class exhibited an adjusted HR of 1.5 (95%CI: 1.3-1.7).…”
Section: Discussionmentioning
confidence: 99%
“…However, assessing only one BMI measure throughout a person's life course may not provide an accurate representation of their BMI changes over time. For this reason, researchers have proposed to study BMI trajectories, that are patterns of changing in BMI over time (De Rubeis et al, 2020; VanWagner et al, 2018; Zeng et al, 2021). The trajectory of BMI is influenced by a range of factors, including genetics, environmental factors, and lifestyle factors such as diet and physical activity (PA), and medical conditions (Clarke et al, 2009; Liu et al, 2018; Werneck et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…After excluding 141 duplicates and 8,160 unrelated articles based on screening of the title and abstract, 112 full-text publications were reviewed for eligibility. Ultimately, 18 articles provided sufficient information and were considered qualified for our meta-analysis (6,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). The 18 cohort studies included 89,094 participants.…”
Section: Study Selectionmentioning
confidence: 99%